Порівняння ігрових рушіїв Unreal Engine та Unity - Лісін, О. А. (ХНУРЕ, 2024)
This work is aimed to dispel an uncertainty about which game engine Unity or Unreal Engine is better for making game applications. There were examined all advantages and disadvantages of both engines: accessibility, graphics capabilities, dedication and additional software. The conclusion was made according to following research based on information from public sources.
Keywords: Unreal Engine; Unity